Comparison of the chronic toxicities of graphene and graphene oxide toward adult zebrafish by using biochemical and phenomic approaches. (1st June 2021) - Audira, Gilbert; Lee, Jiann-Shing; Siregar, Petrus; Malhotra, Nemi; Rolden, Marri Jmelou M.; Huang, Jong-Chin; Chen, Kelvin H.-C.; Hsu, Hua-Shu; Hsu, Yuchun; Ger, Tzong-Rong; Hsiao, Chung-Der
Abstract: Graphene (GR) and graphene oxide (GO) are widely being used as promising candidates for biomedical applications, as well as for bio-sensing, drug delivery, and anticancer therapy. However, their undesirable side effects make it necessary to assess further the toxicity and safety of using these materials. The main objective of the current study was to investigate the toxicities of GR and GO in predicted environmental relevant concentrations in adult zebrafish ( Danio rerio ), particularly on their behaviors, and conducted biochemical assays to elucidate the possible mechanism that underlies their toxicities. Zebrafish was chronically (∼14 days) exposed to two different doses of GR (0.1 and 0.5 ppm) or GO (0.1 and 1 ppm). At 14 ± 1 days, a battery of behavioral tests was conducted, followed by enzyme-linked immunosorbent assays (ELISA) test on the following day to inspect the alterations in antioxidant activity, oxidative stress, and neurotransmitters in the treated zebrafish brain. An alteration in predator avoidance behavior was observed in all treated groups, while GR-treated fish exhibited abnormal exploratory behavior. Furthermore, altered locomotor activity was displayed by most of the treated groups, except for the high concentration of the GR group. From the ELISA results, we discovered a high concentration of GR exposure significantly decreased several neurotransmitters and cortisol levels. Meanwhile, elevated reactive oxygen species (ROS) were displayed by the group treated with low and high doses of GR and GO, respectively. These significant changes would possibly affect zebrafish behaviors and might suggest the potential toxicity from GR and GO exposures. To sum up, the present study presented new evidence for the effects of GR and GO in zebrafish behavioral dysregulation. We hope these assessments can contribute to our understanding of graphene and graphene oxide biosafety. Graphical abstract: Image 1 Highlights: Chronic effect of graphene and graphene oxide in zebrafish behaviors were assessed. Treated groups displayed behavior abnormalities, especially in predator response. Biomarker alterations were shown, especially in the high concentration of graphene group.